The Effectiveness of Learning Biology in The New Normal Period at Senior High School 1 Lalolae - Tri Maniarta Sari; Saparuddin Saparuddin; Raehanatul Jannah; Ernawati Ernawati (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2023)
This study aims to determine the effectiveness of learning biology during the new normal period at Senior High School 1 Lalolae. The effectiveness of learning can be seen from the activities of students during learning takes place, student responses to learning and students' mastery of concepts. This type of research is qualitative with observation and interview methods. The population of class XI students is 30 students. The instruments used in the research were observation sheets and interview sheets. Based on research on the observation sheet of the learning process, a score of 80 was obtained, the second meeting was 100 and the third meeting was scored 100. Meanwhile, the acquisition of the learning behavior observation sheet was obtained by a score of 83, the second meeting was 83 and the third meeting was scored 100. Then, the value of the learning outcomes was 100%. of the 30 students passed. So from these three aspects learning biology during the new normal period can be said to be effective